Zoological diversity associated to a silvopastural system leucaena-guinea grass with different establishment times - Lazo, Jatnel Alonso; Valdés, Nurys Valenciaga; Sampaio, Regynaldo Arruda; Leite, Germano Leão Demolin (Pesquisa Agropecuaria Brasileira, 2007)
The aim of this work was to evaluate the associated zoological diversity of a silvopastural system leucaena-guinea grass, by characterizing the composition and structures of the birds, insects and the macrofauna of the soil, in four establishment times of the silvopastural systems (3, 4, 5 and 6 years of exploitation). For the species recorded in each zoological group, the following ecological indices were determined: number of individuals, richness, diversity and abundance of species, in each establishment times of the system. A significant increase, in all the zoological groups, was observed for the richness of species and for the index of biological diversity of Shannon, as the system developed. An increase in the abundance of bioregulator insects was observed, and for the birds, the sampling time showed no interaction with the different sowing years. The macrofauna of the soil increased during the management of the system, and a dominance of annelids (Polyferetrina elongata and Oligochaeta elegans) was noted during the 6th and 7th year of exploitation. The silvopastural system leucaena-guinea grass increases the biomass production and other biological components, and contributes to create a sustainable system which is compatible with the environment.